Changes in Expected Security Returns, Risk, and the Level of Interest Rates - FERSON, WAYNE E. (Journal of Finance, 1989)
ABSTRACT Regressions of security returns on treasury bill rates provide insight about the behavior of risk in rational asset pricing models. The information in one‐month bill rates implies time variation in the conditional covariances of portfolios of stocks and fixed‐income securities with benchmark pricing variables, over extended samples and within five‐year subperiods. There is evidence of changes in conditional “betas” associated with interest rates. Consumption and stock market data are examined as proxies for marginal utility, in a general framework for asset pricing with time‐varying conditional covariances.